Rare-earth-doped yttria nanoparticles as temperature sensors for whispering-gallery-mode resonators - SANTOS, Rodrigo Galvão dos (2022)
In this thesis, Y2O3 (yttria) nanoparticles (NPs) doped with rare-earth ions, namely Nd3+ and Er3+,Yb3+ are investigated as temperature sensors for whispering-gallery-mode (WGM) res- onators. The ions were chosen to match the available pump lasers for WGM coupling in a silica microsphere, so that multiple sensing parameters can be achieved with a single excitation wave- length. The silica microspheres and the NPs used for this thesis have diameters of about 100 μm and 150 nm respectively. The much smaller size of the NPs with respect to the microspheres ensures that the thermal equilibrium remains undisturbed in the medium of interest (i. e., the microsphere) during the temperature measurements. In order to understand the effects of the lattice vibrations of host materials like yttria on the spectroscopic properties of the active ions, the concept of phonon by quantization of lattice vibration is introduced and the widths and positions of spectral lines of Nd3+ in Y2O3 are discussed as an example of the ion-phonon interactions following a Debye model. Moreover, the theoretical basis of WGMs coupling is derived from the modal equation for a microsphere and some simulations are performed for the system of interest. This system is then considered for temperature sensing applications and the effects of a near-field probe such as a nanoparticle close to the microsphere’s surface are calculated using Rayleigh scattering. Some control experiments were also performed in order to optimize the experimental setup for WGM coupling using the microsphere-prism coupling geometry. A nanothermometer based on single Nd3+:Y2O3 NPs which relies on the ratio of the intensities of the light emitted due to transitions coming from thermally coupled energy levels is presented, followed by another yttria based system, Er3+,Yb3+:Y2O3. Both systems were characterized by exciting single nanoparticles with low power, continuous-wave lasers and the results were described by a rate equation model considering multiphonon interactions. The system presented a relative sensitivity up to 1.36% at 300 K and accuracy of 0.1 K, thus being suited for temperature sensing applications. Finally, some future experiments are proposed for the Nd3+:Y2O3 system, which showed promising results for temperature sensing for microresonators, taking into consideration the theoretical and experimental aspects for both the WGM and luminescence spectroscopy.